2021
DOI: 10.1002/jwmg.22111
|View full text |Cite
|
Sign up to set email alerts
|

A Burning Question: What are the Implications of Forest Fires for Woodland Caribou?

Abstract: Canada's federal recovery strategy for boreal woodland caribou (Rangifer tarandus caribou) classifies areas burned by forest fire as disturbed habitat. This assignment of fire as a disturbance has potential economic and social implications across Canada, and influences plans and actions to achieve caribou conservation and recovery. Previous researchers have reported caribou avoid burned habitat, but these studies did not typically consider unburned residual patches within fire perimeters. Additionally, the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 124 publications
1
5
0
Order By: Relevance
“…In contrast, both buffered linear and polygonal disturbance were avoided in both areas. This builds on recent evidence that the relationship between caribou and fire is complex (Dalerum et al, 2007;DeMars et al, 2019;Konkolics et al, 2021;Skatter et al, 2017) and our study suggests that different habitat characteristics can lead to different responses to fire.…”
Section: Discussionsupporting
confidence: 83%
“…In contrast, both buffered linear and polygonal disturbance were avoided in both areas. This builds on recent evidence that the relationship between caribou and fire is complex (Dalerum et al, 2007;DeMars et al, 2019;Konkolics et al, 2021;Skatter et al, 2017) and our study suggests that different habitat characteristics can lead to different responses to fire.…”
Section: Discussionsupporting
confidence: 83%
“…The impacts of wildfire depend on both the time since the fire and the severity of the fire, although rarely are the diversity of the impacts considered simultaneously, leading to a variety of observed effects on wildlife (Volkmann et al, 2020). For instance, ungulates have been shown to avoid burned areas (Eckrich et al, 2019; Konkolics et al, 2021), select for burned areas (Keay & Peek, 1980; Pearson et al, 1995; Westlake et al, 2020) and show no response or a mixed response to burned areas (Eckrich et al, 2020; Gogan et al, 2019; Long et al, 2008; Roerick et al, 2019). To understand how herbivores repond to burns, it is necessary to consider both the spectrum of fire characteristics and the potential direct and indirect pathways of their effects.…”
Section: Introductionmentioning
confidence: 99%
“…We lack region-specific information on disturbance history, vegetation, and vegetation recovery trajectories post-disturbance that are required for assessing impacts of climate change and anthropogenic disturbance in the RoF (McLaughlin and Webster, 2014;McLaughlin and Packalen, 2021). There may also be variability in caribou responses to fire (Konkolics et al, 2021;Palm et al, 2022) and interactions with predators (Bergerud, 1974) as has been found in other ranges. Disturbance-mediated apparent competition is generally the accepted mechanism for boreal caribou declines across Canada (Festa-Bianchet et al, 2011;Serrouya et al, 2016;Wittmer et al, 2013), but recent studies have noted that apparent competition may be less important in environments where above ground productivity is low because of the absence or lower abundance of other ungulate competitors (Superbie et al, 2022).…”
Section: Discussionmentioning
confidence: 99%